PENGARUH SUBSEKTOR PETERNAKAN (AYAM PEDAGING) TERHADAP KESEMPATAN KERJA DI KABUPATEN KAMPAR PROVINSI RIAU - Muliawandika Syahputra; Dahlan Tampubolon; Sri Endang Kornita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted in Kampar regency, Riau Province. This study aims to determine the factors that affect employment opportunities at farm subsector (broiler) in Kampar, Riau Province. In this data the population and sample are broiler breeders in Kampar Regency, Riau Province. The survey was conducted from March to April 2018 to broiler farmers in Kampar regency, using purposive sampling technique with a sample of 72 respondents. The type of data used in this study is the primary data. The method used in this research is descriptive analysis and quantitative analysis through multiple regression. From the results of research conducted, simultaneous regression test (F test) showed that all independent variables studied have significant influence on employment opportunities in Kampar regency. Partial regression test (t test) showed that DOC, feed and labor variable have positive and significant influence to job opportunity variable. The magnitude of the effect (R2 ) by these three variables together on the dependent variable is 82.4%, while the remaining 17.6% is explained by another variable that is not present in this model.Keywords : Broiler, DOC, Feed, Labor, Job Opportunities, Kampar Regency